IMPLEMENTATION OF TOTAL PHYSICAL RESPONSE METHOD TO IMPROVE ARABIC LANGUAGE LEARNING INTEREST OF GRADE 2 STUDENTS OF DARUSSALAM ELEMENTARY SCHOOL PATNAWITYA, YALA THAILAND - Pocut Silvasya; Salma Hayati; Rokiyah Dolohbongo (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
This study aims to improve the interest in learning Arabic of grade 2 students of Darussalam Elementary School, Patna Witya School, Yala, Thailand, through the Total Physical Response (TPR) method. This study used Classroom Action Research (CAR) which was carried out for three cycles. The subjects of the study were 15 students. The research data were collected through observation techniques using learning interest instruments that had gone through a validation process. Data analysis used quantitative (percentage) and qualitative descriptive. The results showed a significant increase in students' learning interest in each cycle. The percentage of students' learning interest in cycle I was 39% (low), cycle II was 53.1% (moderate) and cycle III was 85.93% (very high). This shows that the TPR method is effective in improving students' learning interest through the integration of physical movement with verbal instructions. The application of the TPR method creates a more dynamic and interactive learning environment, which motivates students to participate actively. Keyword: Total Physical Response Method, Interest In Leraning, Arabic Language